2021
DOI: 10.1101/2021.03.11.435015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dosage sensitivity in Pumilio1-related phenotypes reflects distinct disease mechanisms

Abstract: The RNA-binding protein (RBP) Pumilio1 (PUM1) is associated with two distinct diseases: a late-onset ataxia and a neurodevelopmental syndrome. The ataxia patients retain 75% of normal PUM1 levels, the syndromic patients ~50%, but this seems inadequate to explain the difference in phenotypes. We hypothesized that mild disease results from dysregulation of PUM1 targets, whereas severe disease involves disruption of PUM1 complexes and deregulation of shared targets. We therefore developed a PUM1 interactome for t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 122 publications
(284 reference statements)
0
2
0
Order By: Relevance
“…This possibility is especially relevant in multicellular organisms. Interestingly, a study searching for Pumilio interactors in the murine brain revealed APC/C complex subunits as the main functional category (Botta et al, 2022). Pumilio is a family of RNA-binding proteins that act upstream of developmental processes modulating protein expression in different cells.…”
Section: Apc/c Cdh1/fzr-1 Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility is especially relevant in multicellular organisms. Interestingly, a study searching for Pumilio interactors in the murine brain revealed APC/C complex subunits as the main functional category (Botta et al, 2022). Pumilio is a family of RNA-binding proteins that act upstream of developmental processes modulating protein expression in different cells.…”
Section: Apc/c Cdh1/fzr-1 Regulationmentioning
confidence: 99%
“…interactor in silico (Supplementary data in (Kershner & Kimble, 2010) (Botta et al, 2022). The 3' UTR from fzr-1 has a canonical FBF binding site in the 3' UTR (TGTxxxAT).…”
Section: Elegans Germlinementioning
confidence: 99%